Dendritic spine membrane proteome and its alterations in autistic spectrum disorder - Vallés, Ana Sofía (2022)
Fil: Vallés, Ana Sofía. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Investigaciones Bioquímicas de Bahía Blanca; Argentina